Integrated Management for Active Aging - León Fernández, Maribel (2015)
The Integral Care Program for Older People was born in 2000 in the General Studies Center [Centro de Estudios Generales], in the National University of Costa Rica. Its creation obeyed to promote active aging through teaching, research, extension and production activities. In 2012, the Program was reformulated with the creation of two new projects assigned (UNAVIDA and "Culture and the Artistic Expression as a development way in Older People: Cultural and Artistic Group") and this is how, through integrated management, promoted by the first of these projects, the efforts are concentrated by cross-cutting such as health, awareness and intergenerational interaction and from different populations, institutions and social organizations. The results have been highly beneficial to both the work (maximization of resources) and to the people involved in it, who seek varied and quality learning and integral development opportunities.